2002
DOI: 10.1364/ao.41.005989
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-contrast monitoring of tissue thermal modification

Abstract: Measurements of the contrast value of time-averaged speckle-modulated images of cartilage tissue are used to study tissue thermal modification in the case of laser-light treatment. This modification is related to thermally induced internal stress relaxation in the matrix of the treated tissue. The specific feature of the evolution of time-averaged speckle contrast with a change in the current temperature of modified collagen tissue is the typical looplike form of the contrast-temperature dependencies associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…There are also techniques which evaluate the average speckle contrast coming from the sample. 26 Nevertheless, by its nature most of the biological samples will introduce noise which requires sophisticated filters to remove. 27 In the research work reported here, a nondestructive optical method to study the micro movement and displacements on the feathers is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…There are also techniques which evaluate the average speckle contrast coming from the sample. 26 Nevertheless, by its nature most of the biological samples will introduce noise which requires sophisticated filters to remove. 27 In the research work reported here, a nondestructive optical method to study the micro movement and displacements on the feathers is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Despite speckle theory was established a couple of decades ago [1] , the theoretical formulations had not been transformed into practical instruments in the early years due to technical issues. Recent developments in light sources and registration devices have revived the interest in speckle technologies [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Speckle contrast is defined as the ratio of the standard deviation of light intensity over the average intensity [2] . It is a widely used metrics for many applications such as pavement surface analysis [5] , estimation of tissue optical properties [6] , monitoring of thermal tissue conditions [7] , internal inhomogeneities [8] visualization, viscoelasticity of atherosclerotic plaques measurements [9] , and blood flow evaluation [10] . Contrast can be affected by the light source, the targeted object and the optical system [2] in various ways.…”
Section: Introductionmentioning
confidence: 99%
“…Although the contrast of polychromatic speckle patterns has been used for numerous practical applications, [1][2][3][4][5][6][7][8][9][10][11][12][13] there are still situations, such as Fresnel diffraction, where simple and practical analytical expressions have not yet been derived. To fill this gap we have developed a simple geometrical model utilizing a Fresnel-zone analogy for quantitative estimation of the contrast.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] By measuring its value as a function of either tissue thickness or the coherence length of the light source, the absorption and scattering coefficients of the diffusive media can be derived. 4 Temporal averaging of contrasts for dynamic biospeckle has been used to monitor tissue conditions, 5 visualize internal inhomogeneities, [6][7][8][9] and evaluate blood flow velocity. 10,11 From a metrological point of view, the speckle contrast contains useful information when it differs from unity.…”
Section: Introductionmentioning
confidence: 99%